2015
DOI: 10.1051/fruits/2015016
|View full text |Cite
|
Sign up to set email alerts
|

First finding ofDrosophila suzukii(Matsumura) (Diptera: Drosophilidae) in Apulia, Italy, and its population dynamics throughout the year

Abstract: Introduction. Drosophila suzukii Matsumura (Spotted Wing Drosophila, SWD) is a pest that has been indicated as a major threat to European and Mediterranean fruit production. Its finding in Southern Italy offers interesting data to elaborate an efficient and sustainable control strategy. Materials and methods. The fly was collected during the "overhead" survey of an IAMB organic table grape vineyard by apple vinegar/wine/brown sugar bottle traps placed in and around the field. Once the presence of this pest was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In Italy, it was reported in several other regions along the whole peninsula, including the two major islands Sardinia and Sicily. SWD adult surveys conducted in various fruit orchards of Northwest and Southeast Italy in 2012 and 2013 confirmed that the pest is well established in these regions, and that adult populations decrease considerably in the summer (peaking in late summer/early fall; Baser et al 2015;Mazzetto et al 2015). In France, SWD was found in additional locations in 2010 (Rhones-Alpes) and 2011 (Lorraine, Ile de France, Pays de la Loire, Poitou-Charentes, and Corse) (Withers and Allemand 2012).…”
Section: Southern and Western Europementioning
confidence: 51%
“…In Italy, it was reported in several other regions along the whole peninsula, including the two major islands Sardinia and Sicily. SWD adult surveys conducted in various fruit orchards of Northwest and Southeast Italy in 2012 and 2013 confirmed that the pest is well established in these regions, and that adult populations decrease considerably in the summer (peaking in late summer/early fall; Baser et al 2015;Mazzetto et al 2015). In France, SWD was found in additional locations in 2010 (Rhones-Alpes) and 2011 (Lorraine, Ile de France, Pays de la Loire, Poitou-Charentes, and Corse) (Withers and Allemand 2012).…”
Section: Southern and Western Europementioning
confidence: 51%
“…It has also been reported that D. suzukii may feed on both ripe and unripe fruit particularly on apricot, blackberry, blueberry, cherry, peach, strawberry and other berry fruits (Anonymous, 2012). Baser et al (2015) reported that D. suzukii populations continue throughout the year in southern Italy due to the suitable temperature and moisture, feeding on hosts such as blackberry, fig, grape, jujube, plum and rose hip, and reaching their maximum number in December. Orhan et al (2016) reported D. suzukii in the Erzurum Province in August and September 2014 in strawberry fruit.…”
Section: Resultsmentioning
confidence: 99%
“…The worldwide increase in agricultural product trade with the advancement of international trade and technology has resulted in many invasive species rapidly spreading beyond their original range (Baser et al, 2015(Baser et al, , 2018. Spotted wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), from South Asia (India and Bangladesh), which has attracted significant attention as an invasive species in recent years, was first recorded as a pest of cherry (Prunus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…The location of the Orchard 1, Orchard 2 and Orchard 3 were 36°37′34″N 33°1′9″E, 36°36′7″N 32°56′2″E, 36°37′42″N 33°1′31″E, respectively. Each trap consisted of a 500 ml durable plastic bottles, baited with 100 ml of apple cider vinegar, with five holes 5 mm in diameter on the top sides, to allow the entry of the attracted flies ( Figure 2) (Grassi et al, 2011;Gargani et al, 2013;Baser et al, 2015). Traps were hung at a height of 1.5-2 m on the south-eastern side of tree canopy (Grassi et al, 2011;Labanowska and Piotrowski, 2015;Radonjić and Hrnčić, 2015).…”
Section: Monitoring and Trapping Of Drosophila Suzukiimentioning
confidence: 99%
“…Traps were hung at a height of 1.5-2 m on the south-eastern side of tree canopy (Grassi et al, 2011;Labanowska and Piotrowski, 2015;Radonjić and Hrnčić, 2015). Traps were replaced weekly with new ones and exposed traps were moved to laboratory where collected insects were preserved in 70% ethanol for further analysis (Grassi et al, 2011;Baser et al, 2015).…”
Section: Monitoring and Trapping Of Drosophila Suzukiimentioning
confidence: 99%